Identitas nasional dan multikulturalisme studi kasus di indonesia - Abel, Nabila zahra (Maliki Interdisciplinary Journal, 2025)
Indonesia is an archipelagic country rich in cultural, ethnic, religious, and linguistic diversity. This diversity serves both as a national identity and a challenge in fostering national unity. This article explores the relationship between national identity and multiculturalism in Indonesia using a descriptive qualitative approach. The main issue addressed is how multiculturalism is managed amid social differences and how national identity is formed and strengthened within a pluralistic society. The study presents examples of successful multicultural management in cities such as Medan and Surabaya, as well as failures that led to conflict, such as in Ambon and Sampit. The findings indicate that strengthening national identity requires an inclusive approach, multicultural education, socio-economic equity, and active roles from both the government and the public in promoting intercultural dialogue. Conversely, inequality and intolerance are identified as key factors in the failure of multiculturalism. In conclusion, well-managed multiculturalism can reinforce national identity and serve as a unifying force in a diverse nation.